2006
DOI: 10.1002/eji.200535407
|View full text |Cite
|
Sign up to set email alerts
|

A very rapid and simple assay based on trogocytosis to detect and measure specific T and B cell reactivity by flow cytometry

Abstract: Detection, quantification, separation and characterization of T and B cells reactive to specific antigens are important tasks in both basic and clinical immunology. Here, we describe an approach allowing the performance of all four tasks on a functional basis by flow cytometry. The assay is based on the property of lymphocytes to capture membrane components from the cells they interact with, in a process we call trogocytosis. Working with CD8 + CTL and target cells labeled with membrane markers, we describe th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
75
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(81 citation statements)
references
References 30 publications
5
75
1
Order By: Relevance
“…The peptide-MHC complexes transferred from APCs to T cells are the best studied examples of protein transfer that occurs via trogocytosis. Here, T cells can acquire both MHC class I and class II proteins from APCs (19,23,24,(53)(54)(55). Reports of intercellular transfer of membrane fragments from APCs to T cells (24,54) and from target cells to NK cells (31), and even through homotypic interactions between cells like Daudi cells (56), are consistent with the membrane transfer mechanism that involves the transfer of membrane fragments derived from the intercellular contact or IS (57).…”
Section: Tcr-mediated Internalization and Recyclingmentioning
confidence: 99%
“…The peptide-MHC complexes transferred from APCs to T cells are the best studied examples of protein transfer that occurs via trogocytosis. Here, T cells can acquire both MHC class I and class II proteins from APCs (19,23,24,(53)(54)(55). Reports of intercellular transfer of membrane fragments from APCs to T cells (24,54) and from target cells to NK cells (31), and even through homotypic interactions between cells like Daudi cells (56), are consistent with the membrane transfer mechanism that involves the transfer of membrane fragments derived from the intercellular contact or IS (57).…”
Section: Tcr-mediated Internalization and Recyclingmentioning
confidence: 99%
“…Several important physiological and pathological consequences of trogocytosis in the immune system have been suggested or, in some cases demonstrated (1,2,4). The occurrence of trogocytosis can be evidenced by labeling the APCs' plasma membrane either with fluorescent lipophilic probes such as DiO C18, DiI C18, PKH26, and PKH67, via biotinylation of the proteins, or modified carbohydrate precursors and detecting the presence of these probes onto lymphocytes after their co-culture with APC expressing the antigen (5)(6)(7).…”
mentioning
confidence: 99%
“…For example, the use of fluorescent probes staining either the plasma membrane or the cytosol of APCs revealed that trogocytosis concerns plasma membrane but not cytosolic components (7). In addition, biotinylation of APC surface proteins indicated that only a selected set of these proteins was transferred onto lymphocytes via trogocytosis (6,8).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, we modified the [T‐cell recognition of antigen‐presenting cells (TRAP) by protein capture] assay that measures antigen‐activated cells involved in trogocytosis, i.e., membrane fragments interchange between T cells and APCs during antigen presentation 13 . The TRAP method has been previously used to study trogocytosis in vitro 14 and to determine in vivo T cells specific for herpes virus, 15 lymphocytic choriomeningitis virus, 16 and ovalbumin 14 …”
Section: Introductionmentioning
confidence: 99%